Financial Behavior of Gen Z Students: Digital Lifestyle, FoMo, and Financial Literacy - Prawitasari, Dian; Kadarningsih, Ana; Ahmad, Mubashir (Fakultas Ekonomi, Universitas Semarang, 2025)
The financial behavior of Generation Z is now starting to become worrying. Generation Z is considered a generation that is highly skilled at utilizing digital technology in every online shopping activity so that it tends to be consumptive in daily activities. Generation Z is not yet able to manage finances so that it increases consumptive behavior that will be detrimental to finances in the future. This study aims to examine the factors that influence the financial management behavior of Generation Z, especially students. The factors to be studied include financial literacy, digital lifestyle and fear of missing out in influencing financial management behavior. Data processing uses SEM-PLS analysis with SmartPLS Version 3.2.8 as an analytical tool. The population of this study is Generation Z students who are studying in the city of Semarang. The sample of this study is Generation Z who are still students, amounting to 147 people. The results of this study state that financial literacy has a positive significance on the financial behavior of Generation Z, especially students. Meanwhile, the variables of fear of missing out and digital lifestyle have no influence on financial management behavior in Generation Z who are still students. The results also show that financial literacy is an absolute factor that influences the financial behavior of Generation Z students